Simulations of fluid flow through a porous formation with a single rough fracture plane - Rasouli, A.; Rasouli, Vamegh (ISRM, 2012)
The rock mass, by nature, includes fractures at different scales, which influence the hydro-mechanical behavior of formation. In many engineering applications the formation is porous, for example, tunneling in sandstone layers or production from a sandstone reservoir. The fluid flow in a fractured porous formation would be partly through the formation but the major flow path is the fracture. This, however, depends on different parameters including the formation permeability and more importantly the applied stresses. In this paper, 2D fluid flow simulations are performed using FLUENT on a simple lab scale porous formation which includes one fracture plane. One phase flow with water in a laminar regime was assumed for the analysis. The simulations were conducted for fractures with different surface roughness and also formations with different permeabilities. Also, the fracture aperture was changed to investigate the corresponding effect of applied normal stresses to the fracture plane on permeability. The results indicate how the contribution of fracture in fluid flow reduces at smaller apertures and also larger fracture surface roughness. In general, similar results were observed for larger formation permeabilities.